Classification of Epidemic Community-Acquired Methicillin-Resistant Staphylococcus aureus by Anatomical Site of Isolation. (5th May 2014) - Roberts, Jill C.
Abstract : Methicillin-resistant Staphylococcus aureus contributes significantly to cost, morbidity, and mortality due to infectious disease. We surveyed community-associated MRSA isolates to determine which strains were present within anatomical sites of interest. The most likely sources of MRSA among anatomic sites swabbed were wounds followed by the nasal cavity. The USA 300 MRSA strain was most commonly isolated among wound infections while nasal swabs largely yielded USA 100 MRSA. The frequency of isolation of USA 100 amongst community-associated strains is clinically significant as this strain is often correlated with invasive disease, exhibits broad antibiotic resistance, and has been considered to be hospital associated. The potential of USA 100 to cause serious disease and the frequency of its isolation suggest an important reservoir for opportunistic infection. These data demonstrate that MRSA epidemic clones are widespread among the community.